Intercultural competence development during the adjustment period of Indonesian students in the UK - Erizal Lugman (Indonesian Journal of Applied Linguistics, 2023)
International students must successfully adjust to cross-cultural differences in order to fulfil their academic goals while studying abroad. As a result, students must acquire new skills, especially intercultural competence, in order to properly communicate with people from other cultures. The purpose of this study is to investigate how Indonesian students in UK universities integrate various components of intercultural competence. This study sheds light on why intercultural competence is required and how it is developed. It is grounded in an ethnographic framework involving twelve student blogs and seven student interviews and observations. According to the findings of this study, the intercultural competencies required by Indonesian students in the United Kingdom can be divided into two categories: attitudes and skills. Accepting cultural differences and having an open mind are examples of necessary attitudes. Some necessary skills are the ability to learn new things about a different culture and the ability to follow the rules of the host society. Intercultural competence is distinct and complex phenomenon that have received little academic attention and hence merit additional examination. The data show that during their studies, all of the individuals had difficulty adjusting to cultural differences. According to the findings of this study, Indonesian students studying in the United Kingdom must adjust to cultural differences in order to create favourable views about living abroad. This study serves as evidence that intercultural competence is essential in this situation.